CONTINENTAL COLLISION AND THE DYNAMIC AND THERMAL EVOLUTION OF THE VARISCAN OROGENIC CRUSTAL ROOT - NUMERICAL MODELS - Arnold J.; Jacoby W.R.; Schmeling H.; Schott B. (My University, 2001)
Orogeny is modelled numerically by treating continental collision within full convection solutions, in order to better understand some aspects of the Variscan structures and processes. Three different approaches are taken: (1) collision where one 'continental plate' is 'pushed' against another across a zone of weakness; (2) gravitational instability of a lithospheric mantle root leading to delamination, slab break-off and crustal root reduction; (3) melting in the lower part of a crustal orogenic root. The first approach demonstrates that thick (but in the models: cool) roots can accumulate, in which upper crustal rocks are carried to great depth and mantle material may be carried towards upper crustal levels. The second approach shows that lithospheric root break-off can lead to rapid crustal uplift and thinning of the lower crust if its viscosity is sufficiently low. The third approach suggests that internal heating in a thickened crust may lead to melting and granit formation, however, only after a long geological time (in the order of 100 Ma), while delamination and asthenospheric heat advection may achieve this in shorter time periods (in the order of 10 Ma). The different models tested all demonstrate that crustal root formation and destruction by uplift and exhumation can be achieved in geologically short time periods (1-10 Ma).